Writing to Learn Via Text Chat: Task Implementation and Focus on Form - Nik Aloesnita, Nik Mohd Alwi; Adams, Rebecca; Newton, Jonathan (Elsevier, 2012)
Research has shown that task-based computer-mediated communication(CMC) can foster attention to linguistic form in ways that may promote language learning(c.f., Blake, 2000; Smith, 2003, 2005). However, relatively little research has investigated how differences in the way that tasks are used in CMC settings influence learning opportunities during the task. In an attempt to shed light on the manner in which second language (L2) writing may contribute to L2 development, this chapter presents an empirical study of how two implementation features (degree of task structure and provision of language support) of a writing group task in simultaneous text-CMC influenced learner attention to linguistic form. The analysis draws on data from text chat performance and post-task group interviews to illustrate how aspects of task implementation in a technology-enhanced learning environment may promote attention to language expression and encourage collaborative work on language errors during writing task performance.